Desarrollo de un software educativo para fortalecer el proceso de enseñanza – aprendizaje en el área de la contaminación ambiental por basura “el reciclaje como alternativa para conservar el medio ambiente”, de la asignatura de ciencias naturales para los estudiantes del cuarto año de educación general básica de la unidad educativa “Pedro Vicente Maldonado” de la parroquia El Paraiso de Celén, del cantón Saraguro, provincia de Loja. Periodo lectivo 2013 - 2014 - Ureña Salcedo, Viviana Isabel (2014)
This paper makes an approach to the use of educational software as a teaching tool in the area of environmental education, so that is emerging as the thesis topic "DEVELOPMENT OF AN EDUCATIONAL SOFTWARE FOR STRENGTHENING THE TEACHING - LEARNING AREA ENVIRONMENTAL POLLUTION BY WASTE "RECYCLING AS ALTERNATIVE TO PRESERVE THE ENVIRONMENT" OF COURSE OF NATURAL SCIENCE FOR THE FOURTH YEAR STUDENTS OF BASIC EDUCATION GENERAL EDUCATION "PEDRO VICENTE MALDONADO" UNITY PARISH PARADISE ÇELEN, CANTON SARAGURO, LOJA PROVINCE. LECTIVO PERIOD 2013-2014. The overall objective of this thesis is to contribute to the process of teaching - learning through the development and implementation of an educational software for the subject of Natural Sciences on the theme "ENVIRONMENTAL POLLUTION TRASH, RECYCLING AS ALTERNATIVE TO KEEP ENVIRONMENT. " To comply with the general objective methods such as synthetic, deductive, scientific, likewise for data collection was used techniques as a student survey, interview and observation sheet the teacher who teaches this subject is used, then analysis and interpretation of data was performed, giving answers to the variables found as educational software and the teaching - learning. From the survey of students at the Educational Unit "Pedro Vicente Maldonado" stated that 58% of Natural Science classes are dynamic, 100% said that if they would like to use the educational software and 33% would like the Educational Software contains web links resources. In the interview with the teacher, we must also emphasize the interest placed on the development of research, providing the necessary information as well as the existing documentation on site, to get to the construction of an educational resource that will serve the strengthening the education of students who attend the Education Unit.